Social relationship and academic outcomes: Educational and sociological perspectives (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
This study highlights the connection between social relationships and academic outcomes while framing it within the dual lenses of education and sociology. It emphasizes the interdisciplinary analysis of how interpersonal interactions, peer influences, and social environments shape learning and achievement. It investigates the influence of student-student relationships on academic performance in Social Studies among junior secondary school students in Cross River State, Nigeria. Findings indicate that positive peer relationships significantly enhance academic success, underscoring the role of social interactions in creating a supportive learning environment. When students establish meaningful connections with their peers, they engage in collaborative discussions, share insights, and provide feedback, which enriches their comprehension and critical thinking skills. Additionally, the study identifies student-teacher and student-parent relationships as significant predictors of academic performance. Supportive teacher-student interactions promote active participation and motivation, while active parental involvement reinforces confidence and creates a cohesive support system between home and school. To improve academic performance, schools should: Implement structured group activities that encourage positive peer interactions and collaborative learning in Social Studies. Facilitate regular teacher-student feedback sessions to strengthen trust and engagement. Promote parental involvement through workshops on supporting children’s academic development, ensuring a balanced partnership between home and school.
Keywords: Social relationship; academic performance; social studies; education; students